The teaching and learning of kickboxing: pedagogical recommendations - Da Silva Duarte, Jonatas Deivyson Reis; Oliveira, Sergio Roberto De Lara; Salinas, Johan Andrés Robalino; Tobar, Karen Dennise Lozada; Bueno, João Carlos Alves (Scientific Electronic Archives, 2022)
The training of kickboxing teachers is carried out by federations and confederations with the condition that they acquire a black belt, the highest degree of technical improvement. It has as a prerequisite years of practice in the modality and having passed the colored belt exams. Therefore, teachers are limited to repeating the movements and structures that were passed on by their teachers, without a theoretical and critical training of the teaching and learning process. In this sense, teaching sport to children, adolescents, recreational adults, adult competitors and the elderly are pedagogically different. Children must go through playful activities with diversified motor stimuli, from adolescence onwards there begins to be specialization, recreational adults for specialized training without forceful blows (so as not to injure, as most of them work), adults competitors for situations closer to competition and the elderly for light functional training and without bruising techniques. Other variables should be taken into account when planning lessons, such as student goals, age groups, available materials, and injury history. As it is a contact sport, didactic-pedagogical errors can increase the chances of injuries and dropout of students. Thus, it is important that there is a solid and continuous training on the part of these professionals. In the absence of teaching materials to assist these teachers in the teaching process, this article seeks to bring knowledge of sport pedagogy and recommendations to increase excellence in the teaching-learning process of teacher-students in different age groups in the kickboxing modality.